Serpins in Hemostasis as Therapeutic Targets for Bleeding or Thrombotic Disorders - Bianchini, Elsa P.; Auditeau, Claire; Razanakolona, Mahita; Vasse, Marc; Borgel, Delphine (Frontiers in Cardiovascular Medicine, 2021)
Bleeding and thrombotic disorders result from imbalances in coagulation or fibrinolysis, respectively. Inhibitors from the serine protease inhibitor (serpin) family have a key role in regulating these physiological events, and thus stand out as potential therapeutic targets for modulating fibrin clot formation or dismantling. Here, we review the diversity of serpin-targeting strategies in the area of hemostasis, and detail the suggested use of modified serpins and serpin inhibitors (ranging from small-molecule drugs to antibodies) to treat or prevent bleeding or thrombosis.